Analysis of John Fiske's Semiotics in the Representation of the Journalist Profession in the Japanese Drama 'The Journalist' - Resty Rosy Mena (Program Studi Jurnalistik, Universitas Islam Negeri Raden Fatah Palembang, 2023)
The Journalist profession has an active role in providing information to the public, making the journalist profession interesting to be raised into a movie or drama story. The Journalist is a drama series that airs on Netflix in 2022 with a drama and thriller genre adapted from the 2019 film of the same name The Journalist. Michihito Fujii's drama tells the persistence of a female journalist who is dedicated to her profession as a journalist in exposing problems in government. The purpose of this study is to determine the representation of the journalist profession in the drama series The Journalist. Based on the identification of the problem formulation, this study aims to find out how the codes that appear or are used in the drama The Journalist are interconnected so that a meaning is formed. The method used is descriptive qualitative, which is a method used to describe or explain situations or events. This research uses John Fiske's semiotic model which is divided into three levels, namely the level of reality, the level of representation, and the level of ideology. The unit of analysis chosen in reality is in the form of accessories, environment, gestures, movements, expressions, and costumes, in representation in the form of camera techniques, lighting, music, dialog, action, and characters. The reality and representation displayed form an ideology, which is a meaning contained in the drama The Journalist. Some scenes show the usual activities of a journalist such as finding news, visiting sources, attending press conferences, and making information worthy of disseminating to the public. In practice, journalists often experience difficulties in revealing the truth, especially when facing people who have power.